Fungsi Hukum sebagai Sarana Pengendalian Sosial Masyarakat dalam Rangka Mewujudkan Ketahanan Nasional - Arief Fahmi Lubis (Jurnal Pengabdian Masyarakat Waradin, 2022)
In state life, the law plays a very important role in carrying out community life, The purpose of this study is to show that if there is a violation of the law against the applicable legal regulations, the violated regulations must be enforced, the implementation of the rule of low (law enforcement) in a country is very difficult to separate it from the political aspect of the state. Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description when the research is carried out. The results of this study show that everyone in association in society must pay attention to and implement (obey) legal regulations, in order to create an orderly and peaceful life.